EFFECT OF TEMPERATURE AND BLENDING RATIO TO PRODUCT DISTRIBUTION OF CO-PYROLYSIS LIGNITE AND PALM KERNEL SHELL - Rinny Jelita; Jefriadi Jefriadi; Muhammad Jauhar Mahdi; Muhammad Hafiz (Konversi, 2021)
The issue of the energy crisis and environmental problems due to waste encourage the formation of new fuels from renewable materials such as palm kernel shell biomass (CKS). In other hand, low rank coal (lignite) has low economic value, so it needs to be improved to be used widely. Utilization of lignite and CKS can produce solid products (char) in the form of hybrid coal through the co-pyrolysis process. This study aims to determine the optimum temperature and composition of co-pyrolysis lignite and CKS based on the distribution of the resulting product. The lignite is dried and pulverized to a particle size of 20-50 mesh. CKS cleaned, cut into pieces and sieved to a size of 0.4-2 mm. Then the CKS was dried in an oven at 105oC for 24 hours. Lignite and CKS were mixed with a composition of 15%, 22.5%, and 30% by weight of CKS:lignite. The mixture of materials is put into the co-pyrolysis reactor as much as 200 grams. The co-pyrolysis process was carried out at temperatures of 200ºC, 300ºC, and 400ºC for 1 hour by flowing nitrogen gas into the reactor with a flow rate of 1.5 L/min. The results showed that increasing the mixing ratio of CKS:lignite and co-pyrolysis temperature would increase tar yield while decreasing char yield. Judging from the highest tar yield, the optimum co-pyrolysis temperature was 400oC at 15% optimum mixing ratio, while 200oC and 22.5% were optimum co-pyrolysis temperatures and mixing ratio to obtain the largest char yield. Both tar and char co-pyrolysis products can be an alternative energy source with further processing.